Integration of soil microbiology and metabolomics to elucidate the mechanism of the accelerated infestation of tobacco by the root-knot nematode - Sang, Yinghua; Ren, Ke; Chen, Yi; Wang, Bin; Meng, Yufang; Zhou, Wenbing; Jiang, Yonglei; Xu, Junju (Frontiers in Microbiology, 2024)
Tobacco root-knot nematode (TRKN) disease is a soil-borne disease that presents a major hazard to the cultivation of tobacco, causing significant reduction in crop quality and yield, and affecting soil microbial diversity and metabolites. However, differences in rhizosphere soil microbial communities and metabolites between healthy tobacco soils and tobacco soils with varying degrees of TRKN infection remain unclear. In this study, diseased rhizosphere soils of tobacco infected with different degrees of TRKN [severally diseased (DH) soils, moderately diseased (DM) soils, and mildly diseased (DL) soils] and healthy (H) rhizosphere soils were collected. Here, we combined microbiology with metabolomics to investigate changes in rhizosphere microbial communities and metabolism in healthy and TRKN-infected tobacco using high-throughput sequencing and LC-MS/MS platforms. The results showed that the Chao1 and Shannon indices of bacterial communities in moderately and mildly diseased soils were significantly higher than healthy soils. The Proteobacteria, Actinobacteria, Ascomycota, Burkholderia, Bradyrhizobium and Dyella were enriched in the rhizosphere soil of healthy tobacco. Basidiomycota, Agaricales, Pseudeurotiaceae and Ralstonia were enriched in severally diseased soils. Besides, healthy soils exhibited a relatively complex and interconnected network of bacterial molecular ecologies, while in severally and moderately diseased soils the fungal molecular networks are relatively complex. Redundancy analysis showed that total nitrogen, nitrate nitrogen, available phosphorus, significantly affected the changes in microbial communities. In addition, metabolomics results indicated that rhizosphere soil metabolites were significantly altered after tobacco plants were infected with TRKNs. The relative abundance of organic acids was higher in severally diseased soils. Spearman's analyses showed that oleic acid, C16 sphinganine, 16hydroxyhexadecanoic acid, D-erythro-3-methylmalate were positively correlated with Basidiomycota, Agaricales, Ralstonia. In conclusion, this study revealed the relationship between different levels of TRKN invasion of tobacco root systems with bacteria, fungi, metabolites and soil environmental factors, and provides a theoretical basis for the biological control of TRKN disease.